Chromosome-Scale Genome Assembly for Chinese Sour Jujube and Insights Into Its Genome Evolution and Domestication Signature - Shen, Lian-Ying; Luo, Hang; Wang, Xiao-Ling; Wang, Xue-Meng; Qiu, Xiao-Jing; Liu, Hui; Zhou, Shan-Shan; Jia, Kai-Hua; Nie, Shuai; Bao, Yu-Tao; Zhang, Ren-Gang; Yun, Quan-Zheng; et al. (Frontiers in Plant Science, 2021)
Sour or wild jujube (Ziziphus jujuba Mill. var. spinosa) fruits and dried seeds are popular food all over the world. Here, we report a high-quality genome assembly of sour jujube, with a size of 406 Mbp and scaffold N50 of 30.3 Mbp, which experienced only γ hexaploidization event, without recent genome duplication. Population structure analysis identified four jujube subgroups (two domesticated ones, i.e., D1 in West China and D2 in East/SouthEast China, semi-wild and wild), which underwent an evolutionary history of a significant decline of effective population size during the Last Glacial Period. The respective selection signatures of three subgroups were discovered, such as strong peaks on chromosomes #3 in D1, #1 in D2, and #4 in wild. Genes under the most significant selection on chromosomes #4 in wild were confirmed to be involved in fruit variations among jujube accessions, in transcriptomic analysis. Our study offers novel insights into the jujube population structure and domestication, and pro-vides valuable genomic resources for jujube improvement in stress response and fruit flavor in the future.